ANALYSIS OF STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN SOLVING DIVERGEN MATHEMATICS PROBLEMS IN VIEW OF GENDER DIFFERENCES - Rani Putri Angsi Sormin; Mesak Ratuanik (JURNAL EDUSCIENCE, 2023)
Abstract The ability of mathematics representation os one of the basic skill (ability) that must be had by students. This ability is the ability to tell the mathematics idea as a tool to find solution of mathematics problems. This ability needed by students to understand mathematics concept and to communicate mathematics idea. The purpose of the research was to describe the ability of mathematics representation of male and female students in finishing divergent mathematics problems. Library research was used to complete this research. The result was male students were able to complete divergent mathematics problems in symbolic representation indicator correctly and precisely, but they tend to be difficult in completing verbal representation. Whereas, female students were able to complete divergent mathematics problem on verbal representation indicator correctly and precisely, but they thend to be difficult in completing symolis representation. Â Keywords: representation, divergent msthemstics problem, genderÂ Abstrak Kemampuan representasi matematika merupakan salah satu keterampilan (kemampuan) dasar yang harus dimiliki oleh siswa. Kemampuan ini merupakan kemampuan mengungkapkan ide matematika sebagai alat untuk mencari solusi dari masalah matematika. Kemampuan ini diperlukan oleh siswa untuk memahami konsep matematika dan mengkomunikasikan gagasan matematika. Tujuan penelitian ini adalah untuk mendeskripsikan kemampuan representasi matematika siswa putra dan putri dalam menyelesaikan soal matematika divergen. Penelitian kepustakaan digunakan untuk melengkapi penelitian ini. Hasilnya adalah siswa laki-laki mampu menyelesaikan soal-soal matematika divergen indikator representasi simbolik dengan benar dan tepat, namun mereka cenderung kesulitan dalam menyelesaikan representasi verbal. Sedangkan siswa perempuan mampu menyelesaikan soal matematika divergen pada indikator representasi verbal dengan benar dan tepat, namun kesulitan dalam menyelesaikan representasi simbolis.Kata kunci: representasi, masalah msthemtics divergen, gender